Impact of pulmonary artery pressure on recurrence after catheter ablation in patients with atrial fibrillation - Choi, Yun Young; Choi, Jong-Il; Jeong, Joo Hee; Lee, Hyoung Seok; Kim, Yun Gi; Kim, Mi-Na; Roh, Seung-Young; Shim, Jaemin; Kim, Jin Seok; Park, Seong-Mi; Kim, Young-Hoon (Frontiers in Cardiovascular Medicine, 2023)
The pulmonary veins play a major role in the pathogenesis of atrial fibrillation (AF) and may be affected by cardiac remodeling due to pulmonary vascular dysfunction.Whether pulmonary artery pressure (PAP) is associated with the recurrence of AF after radiofrequency catheter ablation (RFCA) remains undetermined.Methods: Consecutive patients with paroxysmal and persistent AF who underwent RFCA, including wide circumferential pulmonary vein isolation, were analyzed. Systolic PAP was measured using transthoracic echocardiography, and clinical outcomes were compared between patients with PAP <35 mmHg and those with PAP ≥35 mmHg.Results: Among 2379 patients (mean age 56.7±10.6 years, 77% men), 1893 (79.6%) had PAP <35 mmHg and 486 (20.4%) had PAP ≥35 mmHg. During the median follow-up of 25.4 months, in patients with paroxysmal AF (n=1294), the recurrence rate was significantly greater in the PAP ≥35 mmHg group than in the PAP <35 mmHg group (35.1% vs. 23.8%, log-rank p=0.008). However, in patients with persistent AF (n=1085), the recurrence rate was not significantly different between the two groups (52.2% vs. 49.7%, log-rank p=0.409).Multivariate analysis using Cox regression showed that PAP ≥35 mmHg was significantly associated with clinical recurrence (hazard ratio 1.19, 95% confidence interval 1. 02-1.40, p=0.027).This study showed that a higher PAP was associated with an increased risk of recurrence after RFCA in patients with paroxysmal AF, suggesting a mechanism by which a pulmonary vascular pathology may cause impairment of the pulmonary veins and remodeling of the left atrium.